(3OYGA GdJhSds - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3Gddge Efj CSCdc hCJhLg Edjc HfHjc fHj GdQMeI eMeO Udi Gddg Ydjg hSde hBdg, jG CHG GdbGSe jG QShd Gddg jG EeGe GdQMeIs
(3BNQgG (B:s
(3BNQgG(B: (3hbOefGc Hjf jOj LGJfG jG hLjgG YfO Gddg GTaY dfG YfO Gddg Cf JbVj MhGFLj aj GdOfjG hGdBNQI HQMeJc jG CQMe GdQGMejfs
(3jSHbgG GSJZaGQs
(3JHUQI GdeDda (B:s
(3gPG GdOYGA QhGg eMeO Hf HGHhjg Yf GdCFeI GdCWgGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B8: 133s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs